Flow Rate Effects on Microstructure and Mechanical Properties for Titanium Weld Joint - Amir Arifin; Gunawan Gunawan; Dendy Adanta; Ihsan Asura; Imam Syofii; Dewi Puspita Sari (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
Titanium is a metal with a low density, has good heat transfer, and a high melting point; hence widely used for various purposes, such as petrochemicals, aerospace, medical, and reactors. The titanium welding process is complicated because no absence of protection against air during the welding process results in the high absorption of oxygen from free air. In this work, ASTM Gr-1 Titanium is joining using Tungsten Inert Gas (TIG) welding method. The effect of argon flow rate on the mechanical properties of titanium welding and its microstructures is investigated by hardness and tensile tests. Then, microstructure observation to explore the fusion zone and heat-affected zone. Furthermore, phase formation during the welding process is analyzed using the X-ray diffraction (XRD) method. The tensile test revealed that maximum tensile strength was obtained at a 60 l/m argon flow rate while minimum tensile strength was received at 25 l/min. The hardness test shows that maximum hardness was obtained at 25 l/min on the fusion zone.